REIMAGINING CLOUD DATA WAREHOUSING THROUGH SERVERLESS ORCHESTRATION: A REDSHIFT-CENTRIC FRAMEWORK FOR ELASTIC, COST-OPTIMIZED ANALYTICS (Emerging Indexing of Global Multidisciplinary Journal, 2026)
Modern organizations increasingly confront a dual imperative: to extract high-value analytical insight from exponentially growing data volumes while simultaneously containing the spiraling operational and capital expenditures associated with cloud infrastructure. This tension has produced a new generation of data-intensive architectures that merge cloud data warehousing, serverless computing, and event-driven orchestration. Among these, Amazon Redshift–centered ecosystems have emerged as a dominant paradigm for large-scale analytics, yet their economic, architectural, and performance implications remain under-theorized when integrated with contemporary serverless platforms. Building on the design patterns, optimization strategies, and practical recipes documented in Amazon Redshift Cookbook (Worlikar, Patel, & Challa, 2025), this article develops a comprehensive analytical framework that situates Redshift within the broader scholarly discourse on cloud-native and function-as-a-service (FaaS) systems. By synthesizing insights from virtualization research, cost-optimization studies, auto-scaling theory, and stateful serverless architectures, the paper argues that Redshift is no longer merely a static analytical warehouse but a dynamic, programmable analytical substrate capable of being orchestrated through ephemeral compute units.The methodological approach combines an interpretive analysis of the Redshift Cookbook’s architectural recipes with a comparative reading of peer-reviewed research on serverless execution, container provisioning, and storage decoupling. This allows the development of a conceptual model that links Redshift’s columnar, massively parallel processing design with the elasticity and granularity of FaaS. The analysis reveals that when Redshift is paired with services such as AWS Lambda, Step Functions, S3, and stateful orchestration layers, it becomes possible to create data pipelines that are simultaneously cost-adaptive, latency-aware, and resilient to workload volatility. However, these benefits are not automatic. They depend on careful attention to cold-start dynamics, oversubscription risk, data locality, and the complex economic trade-offs of provisioned versus on-demand capacity.